(untitled) (Global Journal of Medical Research, 2021)
The objective of this work was to carry out a review of current regulatory standards, articles, and literature together with a case study, which dealt with the analysis of the conditions of the working environment of an industry, with the focus on workers exposed to chemical agents in manufacturing of carbide cutting tools and products. The method used in this research was qualitative. Technical visits and records of the factory sectors were carried out. With the inspection carried out at the workplace, it is necessary to know the Minimum Required Protection Factor for aerodispersoids ranging from 0.1 to 10 microns and choose the correct Respiratory Protection Equipment, which has an Assigned Protection Factor greater than the exposure dose. The tolerance limit value, 0.005 mg.m-3, for exposure of carbide metallic powders proposed by the ACGIH in 2016, represents a major advance in occupational hygiene and occupational safety, making it possible to carry out the assessment quantitative analysis of the mean concentration of hard metal aerodispersoids.